Improving Learning Achievement in Pancasila and Citizenship Education Through Motivation by Parents in Class VIII Students of SMPN 16 Solok Selatan - Ica Siska Rina; Asril Asril; Budi Juliardi (CV. Rayyan Dwi Bharata, 2022)
This study aims to describe the increase in civics learning achievement through the provision of motivation by parents and to find out the obstacles experienced in an effort to improve learning achievement in Civics subjects. Research methods used are Qualitative with a Descriptive approach that produces descriptive data in the form of written or spoken words from people and behaviors observed by the research location of SMPN 16 Solok Selatan. With observation techniques, interviews by looking for complete and in-depth information and Documentation Studies. Data analysis techniques through observation, interviews and documentation studies. The results of this study show the role of parents to improve learning achievement in providing guidance, providing learning facilities, attention and supervision. Barriers to improving student learning achievement Family Economic Circumstances. Based on the results of this study, it can be concluded that the provision of guidance and providing learning facilities as well as gifts and praise by parents to improve student learning achievement in the subject of Civic Education (Civics) class VIII SMPN 16 Solok Selatan has been carried out, therefore as parents must have a clear picture or strategy about educating and nurturing children,Â directing and educating the child to learn. Providing facilities in learning is one of the supports for children in motivating them to learn. And the existence of gifts and praise is part of the motivation that can affect the level of learning of children and also the obstacles experienced by parents vary from economic difficulties and lack of understanding of parents in educating children because some parents are less educated. If the child lives in a poor family, the child's basic needs are not met and as a result, the child's health is disturbed, so the child's learning is also disrupted.